2017
DOI: 10.1002/pi.5466
|View full text |Cite
|
Sign up to set email alerts
|

Improved flame retardancy by synergy between cyclotetrasiloxane and phosphaphenanthrene/triazine compounds in epoxy thermoset

Abstract: A siloxane compound (MVC) and a bi-group phosphaphenanthrene/triazine compound (TGD) were employed in epoxy thermosets to explore high-efficiency flame retardant systems. With only 1 wt% MVC and 3 wt% TGD, an epoxy thermoset passed UL 94 V-0 rating test and achieved a limiting oxygen index value of 34.0%, exhibiting an excellent flame retardant effect. The MVC/TGD system not only decreased the peak value of heat release rate and effective heat of combustion but also imparted an improved charring ability to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…However, halogenated retardants can produce lots of smoke and toxic gases when they are burning, which have many negative effects on the environment and human . In recent years, researchers have developed many types of halogen‐free flame retardants, such as boron, phosphorus, silicon, sulfur, graphene and nitrogen‐containing compounds . Among them, phosphorus‐containing flame retardant is the most widely used because of its good gaseous phase effect .…”
Section: Introductionmentioning
confidence: 99%
“…However, halogenated retardants can produce lots of smoke and toxic gases when they are burning, which have many negative effects on the environment and human . In recent years, researchers have developed many types of halogen‐free flame retardants, such as boron, phosphorus, silicon, sulfur, graphene and nitrogen‐containing compounds . Among them, phosphorus‐containing flame retardant is the most widely used because of its good gaseous phase effect .…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resins play an indispensable role in almost every industry including aerospace, electric information, insulation, new energy and many other areas owing to their excellent adhesion, chemical resistance and mechanical and dielectric properties. They take about 70% of the market share of thermosetting resins and thus belong to one of the most important species of petrochemical products.…”
Section: Introductionmentioning
confidence: 99%
“…That showed the inhibition effect of TGD on the combustion behavior of epoxy thermoset samples. TGD, which had been confirmed flame retardancy in epoxy thermosets, has better gas‐phase flame retardant effect than condensed‐phase one. In contrast, the results of 3%OMMT/EP sample demonstrated that the addition of OMMT significantly promote the progression of combustion, because of the higher pk‐HRR and av‐EHC values.…”
Section: Resultsmentioning
confidence: 89%
“…The introduction of OMMT caused negative influence for three flame retardant effects aforementioned on 3%OMMT/EP. Differently, because of the stronger flame retardant effect of TGD in gas phase, 3%TGD/EP sample showed a superior flame inhibition effect, but almost no charring effect and worse barrier and protective effect. Comparing with the two samples with only one additive mentioned above, 0.5%OMMT/2.5%TGD/EP sample exhibited the most positive results in all three main effects of flame retardancy, indicating a synergistic effect between OMMT and TGD.…”
Section: Resultsmentioning
confidence: 90%